Effect of mapping characteristic on audiovisual warning: Evidence from a simulated driving study. (February 2022) - Wang, Yuwei; Wu, Bohan; Ma, Shu; Wang, Duming; Gan, Tian; Liu, Hongyan; Yang, Zhen
Abstract: Advanced driver assistance systems (ADAS) can enhance road safety by sending warning signals to drivers. Multimodal signals are gaining attention in ADAS warning design because they offer redundant information that facilitates human–system communication. However, no consensus has been reached on which multimodal design offers optimal benefit to road safety. Icons iconically map the real world and are associated with fast recognition and response time. Therefore, this study aims to investigate whether visual and auditory icons will benefit the effectiveness of audiovisual multimodal warnings. Thirty-two participants (16 females) experienced four types of unimodal warnings (high and low mapping visual warnings and high and low mapping auditory warnings) and four types of audiovisual warnings (high mapping visual + high mapping auditory warning, low mapping visual + low mapping auditory warning, high mapping visual + low mapping auditory warning, and low mapping visual + high mapping auditory warning) in simulated driving conditions. Visual warnings are presented in a head-up display. Results showed that multimodal warnings outperformed unimodal warnings (i.e., modality effect). We found mapping effect in audiovisual warnings, but only high mapping auditory constituents benefited warning effectiveness. Eye movement results revealed that the high mapping constituents might distract drivers from the road. This study adds evidence that multimodal warnings can offer extra benefits to drivers and high mapping auditory signals should be included in multimodal warning design to achieve better driving performance. Highlights: ∙ This study considered the mapping characteristic of audiovisual multimodal warning constituents and tested eight types of warning prototypes in the driving simulator. ∙This study demonstrated the mapping effect of auditory icon in audiovisual warning. ∙This study found the distraction potential of high mapping constituents of multimodal warnings. ∙This study provided suggestions and references for multimodal warning design in the advanced driver assistance systems (ADAS).